Microdeletion del(22)(q12.1) excluding the MN1 gene in a patient with craniofacial anomalies. Issue 2 (6th November 2015) - Bosson, Caroline; Devillard, Françoise; Satre, Véronique; Dieterich, Klaus; Ray, Pierre F.; Morand, Béatrice; Dubois‐Teklali, Fanny; Vieville, Gaëlle; Andrieux, Joris; Brouillet, Sophie; Amblard, Florence; Jouk, Pierre‐Simon; et al.
Abstract : Several studies have recently reported that 22q12.1 deletions encompassing the MN1 gene are associated with craniofacial anomalies. These observations are consistent with the hypothesis that MN1 haploinsufficiency may be solely responsible for craniofacial anomalies and/or cleft palate. We report here the case of a 4‐year‐old boy presenting with global developmental delay and craniofacial anomalies including severe maxillary protrusion and retromicrognathia. Array‐CGH detected a 2.4 Mb de novo deletion of chromosome 22q12.1 which did not encompass the MN1 gene thought to be the main pathological candidate in 22q12.1 deletions. This observation, combined with data from other patients from the Database of Chromosomal Imbalance and Phenotype in Humans Using Ensemble Resources (DECIPHER), suggests that other gene(s) in the 22q12.1 region are likely involved in craniofacial anomalies and/or may contribute to the phenotypic variability observed in patients with MN1 deletion. © 2015 Wiley Periodicals, Inc.